Anticipated and unanticipated monetary variables effectiveness in measuring financial stability in Malaysia during crisis - Caroline Geetha; Roslinah Mahmud; Kok Sook Ching (Penerbit Universiti Malaysia Sabah, 2023)
This study aims to investigate whether the anticipated and unanticipated changes in monetary variables can influence stock returns during a crisis. The financial stability was measured by the stock returns which was the dependent variable of the study. The independent monetary variables used were the interest rate, inflation rate, exchange rate, money supply and the GDP. All the variables were measured in the form of anticipated and unanticipated monetary variables. The analysis began with a unit root test that revealed that both anticipated and unanticipated monetary variables were having unit root problems at level but not at 1st difference. Thus, the variables were found to be integrated at 1st difference. The ARDL method was used to establish the long-run relationship and error correction modelling for the short-run relationship. Monthly data from January 2010 to September 2020 were used. The anticipated monetary variables did have a long-run relationship with stock returns, but all the monetary variables were insignificant at a 5 per cent significance level. However, the anticipated monetary variables did establish a short-run relationship with stock returns. Unfortunately, when unanticipated monetary variables were used both short-run and long-run relationships were established. All the unanticipated monetary variables were significant in explaining the changes in the stock returns except for the unanticipated interest rate.